Metabolic Regulation in the Induction of Trained Immunity - Anaisa V. Ferreira; Jorge Domínguez-Andrés; Laura M. Merlo Pich; Leo A. B. Joosten; Mihai G. Netea (Seminars in Immunopathology, 2024)
The innate immune system exhibits features of memory, termed trained immunity, which promote faster and more robust responsiveness to heterologous challenges. Innate immune memory is sustained through epigenetic modifications, affecting gene accessibility, and promoting a tailored gene transcription for an enhanced immune response. Alterations in the epigenetic landscape are intertwined with metabolic rewiring. Here, we review the metabolic pathways that underscore the induction and maintenance of trained immunity, including glycolysis, oxidative phosphorylation, the tricarboxylic acid cycle, and amino acid and lipid metabolism. The intricate interplay of these pathways is pivotal for establishing innate immune memory in distinct cellular compartments. We explore in particular the case of resident lung alveolar macrophages. We propose that leveraging the memory of the innate immune system may present therapeutic potential. Specifically, targeting the metabolic programs of innate immune cells is an emerging strategy for clinical interventions, either to boost immune responses in immunosuppressed conditions or to mitigate maladaptive activation in hyperinflammatory diseases.

Correction to: Rewiring of glucose metabolism defines trained immunity induced by oxidized low-density lipoprotein - Samuel T. Keating; Laszlo Groh; Kathrin Thiem; Siroon Bekkering; Yang Li; Vasiliki Matzaraki; Charlotte D. C. C. van der Heijden; Jelmer H. van Puffelen; Ekta Lachmandas; Trees Jansen; Marije Oosting; L. Charlotte J. de Bree; et al. (Journal of Molecular Medicine, 2020)

Rewiring of glucose metabolism defines trained immunity induced by oxidized low-density lipoprotein - Samuel T. Keating; Laszlo Groh; Kathrin Thiem; Siroon Bekkering; Yang Li; Vasiliki Matzaraki; Charlotte D. C. C. van der Heijden; Jelmer H. van Puffelen; Ekta Lachmandas; Trees Jansen; Marije Oosting; L. Charlotte J. de Bree; et al. (Journal of Molecular Medicine, 2020)
Stimulation of monocytes with microbial and non-microbial products, including oxidized low-density lipoprotein (oxLDL), induces a protracted pro-inflammatory, atherogenic phenotype sustained by metabolic and epigenetic reprogramming via a process called trained immunity . We investigated the intracellular metabolic mechanisms driving oxLDL-induced trained immunity in human primary monocytes and observed concomitant upregulation of glycolytic activity and oxygen consumption. In two separate cohorts of healthy volunteers, we assessed the impact of genetic variation in glycolytic genes on the training capacity of monocytes and found that variants mapped to glycolytic enzymes PFKFB3 and PFKP influenced trained immunity by oxLDL. Subsequent functional validation with inhibitors of glycolytic metabolism revealed dose-dependent inhibition of trained immunity in vitro. Furthermore, in vivo administration of the glucose metabolism modulator metformin abrogated the ability for human monocytes to mount a trained response to oxLDL. These findings underscore the importance of cellular metabolism for oxLDL-induced trained immunity and highlight potential immunomodulatory strategies for clinical management of atherosclerosis. Key messages Brief stimulation of monocytes to oxLDL induces a prolonged inflammatory phenotype. This is due to upregulation of glycolytic metabolism. Genetic variation in glycolytic genes modulates oxLDL-induced trained immunity. Pharmacological inhibition of glycolysis prevents trained immunity.

Interferon-γ and CXCL10 responses related to complaints in patients with Q fever fatigue syndrome - Ruud P. H. Raijmakers; Anne F. M. Jansen; Stephan P. Keijmel; Teske Schoffelen; Anja Scholzen; Jos W. M. van der Meer; Leo A. B. Joosten; Mihai G. Netea; Marcel van Deuren; Chantal P. Bleeker-Rovers (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Patients with type 1 diabetes mellitus have impaired IL-1β production in response to Mycobacterium tuberculosis - E. Lachmandas; K. Thiem; C. van den Heuvel; A. Hijmans; B. E. de Galan; C. J. Tack; M. G. Netea; R. van Crevel; J. A. van Diepen (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Bacillus Calmette-Guérin vaccination at birth and in vitro cytokine responses to non-specific stimulation. A randomized clinical trial - T. N. Nissen; N. M. Birk; B. A. Blok; R. J. W. Arts; A. Andersen; J. Kjærgaard; L. M. Thøstesen; T. Hoffmann; D. L. Jeppesen; S. D. Nielsen; P.-E. Kofoed; L. G. Stensballe; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Soluble TLR2 and 4 concentrations in cerebrospinal fluid in HIV/SIV-related neuropathological conditions - Khutso M. Mothapo; J. ten Oever; P. Koopmans; F. F. Stelma; S. Burm; J. Bajramovic; M. M. Verbeek; M. G. Olde Rikkert; M. G. Netea; G. Koopman; A. J. van der Ven (Journal of NeuroVirology, 2017)

Association of a variable number tandem repeat in the NLRP3 gene in women with susceptibility to RVVC - M. Jaeger; A. Carvalho; C. Cunha; T. S. Plantinga; F. van de Veerdonk; M. Puccetti; C. Galosi; L. A. B. Joosten; B. Dupont; B. J. Kullberg; J. D. Sobel; L. Romani; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Individualized significance of the −251 A/T single nucleotide polymorphism of interleukin-8 in severe infections - M. D. Georgitsi; V. Vitoros; C. Panou; I. Tsangaris; E. Aimoniotou; N. K. Gatselis; E. Chasou; G. Kouliatsis; K. Leventogiannis; D. Velissaris; E. Belesiotou; O. Dioritou-Aggaliadou; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Recurrent candidiasis and early-onset gastric cancer in a patient with a genetically defined partial MYD88 defect - Ingrid P. Vogelaar; Marjolijn J. L. Ligtenberg; Rachel S. van der Post; Richarda M. de Voer; C. Marleen Kets; Trees J. G. Jansen; Liesbeth Jacobs; Gerty Schreibelt; I. Jolanda M. de Vries; Mihai G. Netea; Nicoline Hoogerbrugge (Familial Cancer, 2016)

The RIG-I-like helicase receptor MDA5 (IFIH1) is involved in the host defense against Candida infections - M. Jaeger; R. van der Lee; S.-C. Cheng; M. D. Johnson; V. Kumar; A. Ng; T. S. Plantinga; S. P. Smeekens; M. Oosting; X. Wang; W. Barchet; K. Fitzgerald; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Polymorphisms in cytokine genes IL6, TNF, IL10, IL17A and IFNG influence susceptibility to complicated skin and skin structure infections - M. H. T. Stappers; Y. Thys; M. Oosting; T. S. Plantinga; M. Ioana; P. Reimnitz; J. W. Mouton; M. G. Netea; L. A. B. Joosten; I. C. Gyssens (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Association of autophagy-related 16-like 1 (ATG16L1) gene polymorphism with sepsis severity in patients with sepsis and ventilator-associated pneumonia - A. Savva; T. S. Plantinga; A. Kotanidou; M. Farcas; F. Baziaka; M. Raftogiannis; S. E. Orfanos; G. Dimopoulos; M. G. Netea; E. J. Giamarellos-Bourboulis (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Autophagy is redundant for the host defense against systemic Candida albicans infections - S. P. Smeekens; R. K. Malireddi; T. S. Plantinga; K. Buffen; M. Oosting; L. A. B. Joosten; B. J. Kullberg; J. R. Perfect; W. K. Scott; F. L. van de Veerdonk; R. J. Xavier; E. van de Vosse; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Circulating galectin-3 in infections and non-infectious inflammatory diseases - J. Oever; E. J. Giamarellos-Bourboulis; F. L. Veerdonk; F. F. Stelma; A. Simon; M. Janssen; M. Johnson; A. Pachot; B.-J. Kullberg; L. A. B. Joosten; M. G. Netea (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

The impact of caspase-12 on susceptibility to candidemia - D. C. Rosentul; T. S. Plantinga; W. K. Scott; B. D. Alexander; N. M. D. van de Geer; J. R. Perfect; B. J. Kullberg; M. D. Johnson; M. G. Netea (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Mycoviruses: future therapeutic agents of invasive fungal infections in humans? - W. W. J. Sande; J. R. Lo-Ten-Foe; A. Belkum; M. G. Netea; B. J. Kullberg; A. G. Vonk (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

The role of interferon-gamma in the increased tuberculosis risk in type 2 diabetes mellitus - J. E. Stalenhoef; B. Alisjahbana; E. J. Nelwan; J. Ven-Jongekrijg; T. H. M. Ottenhoff; J. W. M. Meer; R. H Nelwan; M. G. Netea; R. Crevel (European Journal of Clinical Microbiology & Infectious Diseases, 2008)